2017
DOI: 10.1002/cbf.3292
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophage migration inhibitory factor (MIF) in the effects of oxidative stress on human retinal pigment epithelial cells

Abstract: Proliferative vitreoretinopathy (PVR) is the major cause of treatment failure in individuals who undergo surgery for retinal detachment. The epithelial‐mesenchymal transition (EMT) in retinal pigment epithelium (RPE) cells contributes to the pathogenesis of PVR. Oxidative stress is thought to play a role in the progression of retinal diseases including PVR. We have now examined the effects of oxidative stress on the EMT and related processes in the human RPE cell line. We found that H2O2 induced the contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Consistent with our findings, Huang et al found delayed reformation of tight junctions in a diabetic rat model [17]. It is well documented in other cell types that increased oxidative stress can result in decreased expression of tight junction proteins [37][38][39][40]. In the present study, not only did antioxidant treatment restore CEC proliferation and migration under diabetic conditions, NAC also improved both TEER values and ZO-1 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings, Huang et al found delayed reformation of tight junctions in a diabetic rat model [17]. It is well documented in other cell types that increased oxidative stress can result in decreased expression of tight junction proteins [37][38][39][40]. In the present study, not only did antioxidant treatment restore CEC proliferation and migration under diabetic conditions, NAC also improved both TEER values and ZO-1 expression.…”
Section: Discussionsupporting
confidence: 93%
“…The assay was conducted as previously described 14,31,43,45 with some modifications. The assay was conducted as previously described 14,31,43,45 with some modifications.…”
Section: Collagen Gel Contraction Assay (Threedimensional Cell Cultmentioning
confidence: 99%
“…Furthermore, the level of MiF has been found to be upregulated in the vitreous in PVr patients (22). recent results implicate MiF in the induction of epithelial-mesenchymal transition (eMT) and its related processes by oxidative stress in human RPE cells, and MIF was reported to regulate expression of EMT markers (41). In the present study, our data revealed that recombinant MiF increased the expression of IL-6 and MCP-1 in human RPE cells, which suggests that MIF plays a proinflammatory role in the development of PVR.…”
Section: Discussionmentioning
confidence: 94%